Improved understanding of transverse galloping of rectangular cylinders. Issue 221 (February 2022) - Liu, Y.Z.; Ma, C.M.; Dai, K.S.; El Damatty, A.; Li, Q.S.
Abstract: This paper investigates transverse galloping of rectangular cylinders characterized by 0.7< B / D  < 2.8 ( B : width; D : depth) in uniform flows at relatively high Reynolds numbers ( ≫ 10 3 ), in which the oscillation is self-excited and the phenomenon is triggered from rest. First, a better understanding of potential links between static and dynamic transverse galloping issues is acquired using a novel viewpoint that considers key characteristic points on the static force and dynamic response curves. Then, new perspectives on the transverse galloping generation mechanism are presented. Analysis of the present study indicates that the traditional and most widely known time-averaged flow pattern approach is not sufficient to explain possible transverse galloping physical mechanisms. A new time-varying flow pattern approach is needed and is proposed in this paper. This new approach shows that a quantitative change in the occurrence ratio of intermittent reattachment flow, which leads to a qualitative change in the time-varying flow pattern type, is the generation mechanism for certain important, interesting static and transverse galloping dynamic behaviors. Highlights: Qualitative and quantitative relationships exist between characteristic points on the static and dynamic curves. A time-varying flow pattern viewpoint is necessary to fully explain possible transverse galloping mechanisms. Characteristic points on the static and dynamic curves are generated by qualitative changes in time-varying flow patterns.